Sauh Ferry Services Sdn. Bhd. / Salma Yahya... [et al.] - Yahya, Salma; Adam, Nurul Ilham; Mohamed, Nurul Aini; Kathar Ismail, Siti Khatijah; Mohd Noordin, Idzyani Zalilah (2003)
Sauh Ferry Services Sdn. Bhd. is a private limited company that is registered with Registrar of Company. The business is between 5 shareholders that are contributing RM900000 as capital, which is 40% is contribute by the General Manager and the others are 15%. The company also seeks the rest of capital by applying loan from Bumiputra Commerce Sdn. Bhd, amounted RM800000. The total capital that we need for operating this business is RM1.7 million. Our business premise, also as the main office is at PT 2457, Jln. Kg. Perak, 02000, Kuala Perlis, Perlis. We have choose this location because it is near to the Kuala Perlis Jetty, that will make us easier to manage the public affairs and operate our ferry service Our ferry services are kindly different from the existing ferries services in Kuala Perlis. Our ferries are specially designed for passenger and vehicles. These ferries have two layers, the upper layers are designed for the passenger and the lower layers are for the vehicles (cars and motorcycles). For one horizontal area, it is about 126m². So, for double horizontal area it is about 252m². The lower layer that is for the vehicles can be fill about 25 cars and 15 motorcycles. However, in the first layer that is for the passengers we have provided 50 seats